2018
DOI: 10.1111/twec.12701
|View full text |Cite
|
Sign up to set email alerts
|

Did foreign exchange holding influence growth performance during the global financial crisis?

Abstract: In a context of increased foreign exchange reserves holding from emerging and developing countries, this paper investigates the diminishing return of reserves holding assumption over the most severe phase of the global financial crisis (2008Q1–2010Q4). Relying on a Panel Smooth Transition Regression model, we highlight the differential effect of the accumulation of foreign exchange reserves for a set of financial vulnerabilities variables. In a specific manner, although reserves accumulation is effective above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…An analysis of the impact of FER on the microeconomic variables is significant and uses a pure-sign restriction approach and summarizes that the FER amount must be justified with the need of a nation (Nie, 2017). It is suggested that FER must be from the source that is sympathetic in absorbing the financial crisis shocks (Allegret & Allegret, 2018).…”
Section: Review Of Earlier Studiesmentioning
confidence: 99%
“…An analysis of the impact of FER on the microeconomic variables is significant and uses a pure-sign restriction approach and summarizes that the FER amount must be justified with the need of a nation (Nie, 2017). It is suggested that FER must be from the source that is sympathetic in absorbing the financial crisis shocks (Allegret & Allegret, 2018).…”
Section: Review Of Earlier Studiesmentioning
confidence: 99%